Non-isothermal crystallization of poly(trimethylene terephthalate)/single-walled carbon nanotubes nanocomposites - Szymczyk, A.; Roslaniec, Z. (Polimery, 2012)
In this work, non-isothermal crystallization behavior of nanocomposites based on poly(trimethylene terephthalate) (PTT) and single-walled carbon nanotubes (SWCNTs) and neat PTT was studied in order to determine the effects of SWCNTs on its crystallization behavior. Nanocomposites with 0.3 and 0.5 wt. % of SWCNTs were studied. Using of SAXS and DSC methods, the nanostructure of PTT/SWCNTs nanocomposites and neat PTT was investigated in real time in the process of crystallization from the melt. The correlation function approach was used to analyze SAXS data. Changes in long period values, thickness of crystalline lamellae, thickness of amorphous layers, degree of crystallinity during cooling from the melt were discussed.